Please look after Mom : a novel - Sin, Kyong-suk.; Kim, Chi-Young. (New York : Alfred A. Knopf, 2011)
Follows the efforts of a family to find the mother who went missing from Seoul Station and their sobering realizations when they recall memories that suggest she may not have been happy.
Keywords: Mothers -- Fiction; Families -- Fiction; Sacrifice -- Fiction; Seoul (Korea) -- Fiction